TAM Model for E-Health Implementation in Rural Areas of Uttarakhand, Post Covid-19 Pandemic - Pushpa Kataria; G.P. Dang; Divneet Kaur; Prashant Singh; Vijay Prakash Gupta (ACHSM, 2021)
Objective: The present study aim to find out the factors that has an influence and impacts the actual use of e-Health during post COVID-19 pandemic on the lines of TAM (technology acceptance model) and further suggest ways for effective implementation and adoption of e-Health by the rural patients. Design & Setting: The study was conducted on a total of 243 rural patients who had experienced e-Health services. Structural Equation Modeling has been used for analysis of data. Results: The analysis revealed that 'perceived usefulness', 'perceived ease of use', 'privacy' and 'trust', all had considerable impact on the 'intention to use' which further significantly  impacts the 'actual use'. Conclusion: Using in-depth interviews, both patients and physicians, practice of evidence-based e-Health interventions was identified for effective implementation and adoption of e-Health, which further helps to provides an equitable healthcare services to both urban and rural population.